What voice do British workers want? - Bryson, Nigel; Freeman, Richard Barry (London, 2006)
"The problems/need for representation and participation reported by workers vary across workplaces and by types of jobs. Workers with greater workplace needs are more desirous of unions but their preferences are fine-grained. Workers want unions to negotiate wages and work conditions and for protection but do not see unions as helping them progress in their careers. Many workers see no major workplace problems that would impel them to form or join unions. Unionism raises reported problems while firm-based non-union channels of voice reduce reported problems, but unions that work effectively with management and those that have sufficient strength to be taken seriously by management reduce the number of problems at union workplaces."